2020
DOI: 10.1186/s12888-020-02796-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of anxiety and depressive symptoms among patients diagnosed with oral cancer in China: a cross-sectional study

Abstract: Background: Anxiety and depression are common mental health problems among patients with cancer. While many psychological variables have been proven to influence anxiety and depressive symptoms, the variables are not mutually exclusive and their integrated effects on patients with oral cancer are yet unknown. The present study aims to explore the prevalence of anxiety and depressive symptoms among patients with oral cancer, to find out key potentially predictive factors associated with anxiety and depressive s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 53 publications
3
21
0
Order By: Relevance
“…Our result that perceived stress made an important contribution to the anxiety and depressive symptoms was also consistent with previous studies both during ( 49 ) and before ( 19 , 20 ) the outbreak in students and other populations ( 50 , 51 ). In the current study, the only psychological variable in the regression was perceived stress.…”
Section: Discussionsupporting
confidence: 93%
“…Our result that perceived stress made an important contribution to the anxiety and depressive symptoms was also consistent with previous studies both during ( 49 ) and before ( 19 , 20 ) the outbreak in students and other populations ( 50 , 51 ). In the current study, the only psychological variable in the regression was perceived stress.…”
Section: Discussionsupporting
confidence: 93%
“…A convenience sample of nurses from the School and Hospital of Stomatology, China Medical University, participated in the survey. The sample size [ 21 – 23 ] was calculated as follows: . The parameters were α = 0.05, Zα = 1.96, σ = 14.12, δ = 2. n = 1.96 2 * 14.12 2 /2 2 = 191.48.…”
Section: Methodsmentioning
confidence: 99%
“…We found that shape change and impaired physical function were important drivers of stigma, which was consistent with previous ndings [21] . Many patients were prone to stigma owing to body image loss, reduced self-esteem, and a sense of shame, and postoperative oral cancer patients were especially susceptible because of the facial deformity and dysfunction they experience [4,22] . Importantly, facial dis gurement was consistently associated with the development of stigma and the perception of stigma [23] .…”
Section: Discussionmentioning
confidence: 99%